Targeting γc family cytokines with biologics: current status and future prospects - Fabian Bick; Christophe Blanchetot; Bart N. Lambrecht; Martijn J. Schuijs (mAbs)
Over the recent decades the market potential of biologics has substantially expanded, and many of the top-selling drugs worldwide are now monoclonal antibodies or antibody-like molecules. The common gamma chain (γc) cytokines, Interleukin (IL-)2, IL-4, IL-7, IL-9, IL-15, and IL-21, play pivotal roles in regulating immune responses, from innate to adaptive immunity. Dysregulation of cell signaling by these cytokines is strongly associated with a range of immunological disorders, which includes cancer as well as autoimmune and inflammatory diseases. Given the essential role of γc cytokines in maintaining immune homeostasis, the development of therapeutic interventions targeting these molecules poses unique challenges. Here, we provide an overview of current biologics targeting either single or multiple γc cytokines or their respective receptor subunits across a spectrum of diseases, primarily focusing on antibodies, antibody-like constructs, and antibody-cytokine fusions. We summarize therapeutic biologics currently in clinical trials, highlighting how they may offer advantages over existing therapies and standard of care, and discuss recent advances in this field. Finally, we explore future directions and the potential of novel therapeutic intervention strategies targeting this cytokine family.